Workshop Pengelolaan Pembelajaran berbasis Culturally Responsive Teaching bagi Guru di SDN 2 Puyung - Saidah, Karimatus; Permana, Erwin Putera; Basori, Muhamad; Imron, Ilmawati Fahmi; 'Adziima, Mavatih Fauzul; Muliawati, Astri; Mustofa, Muhammad Afif (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2026)
This Community Service (PkM) program addresses the low cultural awareness and lack of cultural integration in learning at SDN 2 Puyung, Trenggalek. This mountainous school needs to strengthen students' character and local cultural identity as a preparation for the future. The solution implemented was a Culturally Responsive Teaching (CRT)-based learning management workshop, aimed at improving cultural literacy and teacher competency. The training included an introduction to the CRT concept, its benefits, and a simulation of integrating local cultural potential into the subject matter. The implementation method for this service included observation and coordination, training, mentoring, and evaluation. The PkM results showed a positive response from the 13 participating teachers. They gained insight into how culture encompasses values, traditions, and perspectives, as well as the importance of cultural integration in creating meaningful learning, fostering appreciation for local culture, and preserving it from foreign influences. This activity successfully improved teachers' understanding of cultural literacy and their readiness to implement CRT.